2010
DOI: 10.1021/jp910641s
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Dynamics of Hyperthermal Oxygen Atoms on Ionic Liquid Surfaces: [emim][NTf2] and [C12mim][NTf2]

Abstract: Collisions of hyperthermal oxygen atoms, with an average laboratory-frame translational energy of 520 kJ mol−1, on continuously refreshed ionic liquids, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide ([emim][NTf2]) and 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide ([C12mim][NTf2]), were studied with the use of a beam-surface scattering technique. Time-of-flight and angular distributions of inelastically scattered O and reactively scattered OH and H2O were collected for variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
113
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(127 citation statements)
references
References 64 publications
14
113
0
Order By: Relevance
“…In particular, the oxygen scattering studies have highlighted the presence of anions in the interfacial region. 26,49 The current results from NO + RTIL collisional scattering, which should be similarly sensitive to the composition of the very topmost layers of the liquid, strongly support and confirm the above expectations that anions are present at the interface. This is immediately clear from the fact that the choice of RTIL counteranion has a strong effect on both the rotational and spin−orbit electronic distributions of the scattered NO products.…”
Section: Resultssupporting
confidence: 82%
“…In particular, the oxygen scattering studies have highlighted the presence of anions in the interfacial region. 26,49 The current results from NO + RTIL collisional scattering, which should be similarly sensitive to the composition of the very topmost layers of the liquid, strongly support and confirm the above expectations that anions are present at the interface. This is immediately clear from the fact that the choice of RTIL counteranion has a strong effect on both the rotational and spin−orbit electronic distributions of the scattered NO products.…”
Section: Resultssupporting
confidence: 82%
“…14,[16][17][18] Complementing the established techniques, we have developed an alternative approach based on reactive-atom scattering (RAS), combined either with mass spectrometric (RAS-MS) or laser-induced fluorescence (RAS-LIF) detection. [18][19][20][21][22][23][24][25][26] The essence of this method, of which the RAS-LIF variant is the one we use here, is that projectiles interrogate the liquid surface via selective reaction with specific functional groups, producing a gas-phase product which is detected quantitatively. The dynamical attributes of these products confirm that they originate in the extreme outer layers of the liquid.…”
Section: Introductionmentioning
confidence: 99%
“…1 3 ] surface we found that the anion is more abundant at the surface than the cation and that the ethyl-chains that lie on the surface tend to stick up towards the vacuum [37]. However, we found that there exists a slightly different surface topology for [emim][NTf 2 ], which includes a larger anion that keeps the ethyl chain from protruding out of the surface [36]. In contrast, the surface of [C 12 mim][NTf 2 ] has long hydrocarbon chains sticking up into the vacuum, causing a noticeable difference in the reaction profile that occurs upon gaseous atom collision.…”
Section: Building a Model Liquid Surfacementioning
confidence: 73%
“…This means that there are readily accessible H atoms sticking up out of the surface for H abstraction or H elimination reactions to occur before the incident O crosses the surface threshold (the point where the density is equal to half the bulk density). Our study was done in tandem with Minton and coworker's similar experimental study [36] 3 ] surface causing minor changes in the local chemistry as shown in Table 1. Nearly all of the incident Ar atoms scatter from the surface (a probability of 0.91) with a small fraction trapped at the end of the simulation time of 7.3 ps.…”
Section: [Emim][no 3 ]mentioning
confidence: 99%
See 1 more Smart Citation